Quantum entangled-probe scattering theory. (10th August 2021) - Irfan, Abu Ashik Md; Blackstone, Patrick; Pynn, Roger; Ortiz, Gerardo
Abstract: We develop an entangled-probe scattering theory, including quantum detection, that extends the scope of standard scattering approaches. We argue that these probes may be revolutionary in studying entangled matter such as unconventional phases of strongly correlated systems. Our presentation focuses on a neutron beam probe that is mode-entangled in spin and path as is experimentally realized by Shen et al (2020 Nat. Commun. 11 930), although similar ideas also apply to photon probes. We generalize the traditional van Hove theory (van Hove 1954 Phys. Rev. 95 249) whereby the magnetic response is written as a properly-crafted combination of two-point correlation functions. Tuning the probe's entanglement length allows us to interrogate spatial scales of interest by analyzing interference patterns in the differential cross-section. Remarkably, for a spin dimer target we find that the typical Young-like interference pattern observed if the target state is un-entangled gets quantum erased when that state becomes maximally entangled.